MRI UNDERESTIMATES PRESENCE AND SIZE OF KNEE OSTEOPHYTES USING CT AS A REFERENCE STANDARD - Roemer, Frank; Engelke, Klaus; Laredo, J. -D.; Li, L.; Guermazi, A. (OSTEOARTHRITIS AND CARTILAGE, 2022)
The radiographic diagnosis of knee osteoarthritis (OA) is based on the presence of a definite osteophyte (OP) on the a.p. or p.a. radiograph. OPs represent fibrocartilaginous and skeletal outgrowths that are frequently localized at the joint margins, but central osteophytes may also be observed, especially at the femoral notch. Epidemiologic studies and clinical trials commonly employ MRI using standard clinical sequences and OP assessment is one of the features included in whole organ ordinal OA grading. Commonly used sequence protocols in such studies are based on triplanar fat suppressed T2- or proton density-weighted sequences with bony features as well as fibrous and lipomatous tissues appearing hypointense. This may potentially result in underestimation of such features including osteophyte assessment. Computed tomography (CT), another tomographic technique is considered as the modality of choice for the analysis of mineralized structures such as OPs and may therefore be used as a reference standard for other modalities assessing these structures. Thus, the aim of the current study was to explore the diagnostic performance of routine MRI as used in observational studies and clinical trials of knee OA for the assessment of OPs in all three knee compartments and the femoral notch using CT as a reference standard.<br
CRIS-Team WoS Importer:2022-04-22